Fluctuations of Atmospheric Pressure and the Sound of Underground Karst Systems: The Antro del Corchia Case (Apuane Alps, Italy) - Badino, Giovanni; Chignola, Roberto (Frontiers in Earth Science, 2019)
Mountains that contain subterranean voids can inhale fresh and clean air, and their breath is a fascinating natural phenomenon that speleologists know very well. Air flow through the entrances of underground systems is also an interesting geophysical problem. Basically it is caused by temperature and pressure gradients between the internal and external atmospheres, but the dynamic interplay between these two driving forces is still not well understood. We contribute to dissect out the physics of underground winds. Wind velocity, internal and external temperature and pressure have been measured synchronously at two entrances of the vast (~64 km) underground system beneath the Mount Corchia, Apuane Alps, Italy. The data show that, within time scales of minutes to days, pressure fluctuations of the external atmosphere primarily force air to flow underground, whereas temperature gradients play only a minor role. We model the cave as a system that takes the external atmospheric pressure as the input signal and outputs wind from its entrances. This wind, on its turn, contain information about the system's response, and hence on the structure of the subterranean voids. This information can be extracted by standard signal processing techniques, and using deconvolution methods we identify the same infrasound resonances in signals sampled at both entrances. These are the characteristic frequencies of the cave, and by using the Helmholtz resonance formalism it can be estimated that the explored volume of this important underground system is less than a half of its probable real extension.